An Assessment of Anesthesia Capacity in Liberia: Opportunities for Rebuilding Post-Ebola. (12th April 2021) - Odinkemelu, Didi S.; Sonah, Aaron K.; Nsereko, Etienne T.; Dahn, Bernice T.; Martin, Marie H.; Moon, Troy D.; Niconchuk, Jonathan A.; Walters, Camila B.; Kynes, J. Matthew
Abstract : BACKGROUND: The health system of Liberia, a low-income country in West Africa, was devastated by a civil war lasting from 1989 to 2003. Gains made in the post-war period were compromised by the 2014–2016 Ebola epidemic. The already fragile health system experienced worsening of health indicators, including an estimated 111% increase in the country's maternal mortality rate post-Ebola. Access to safe surgery is necessary for improvement of these metrics, yet data on surgical and anesthesia capacity in Liberia post-Ebola are sparse. The aim of this study was to describe anesthesia capacity in Liberia post-Ebola as part of the development of a National Surgical, Obstetric, and Anesthesia Plan (NSOAP). METHODS: Using the World Federation of Societies of Anaesthesiologists (WFSA) Anaesthesia Facility Assessment Tool (AFAT), we conducted a cross-sectional survey of 26 of 32 Ministry of Health recognized hospitals that provide surgical care in Liberia. The surveyed hospitals served approximately 90% of the Liberian population. This assessment surveyed infrastructure, workforce, service delivery, information management, medications, and equipment and was performed between July and September 2019. Researchers obtained data from interviews with anesthesia department heads, medical directors and through direct site visits where possible. RESULTS: Anesthesiologist and nurse anesthetist workforce densities were 0.02 and 1.56 per 100, 000 population, respectively, compared to 0.63 surgeons per 100, 000 population and 0.52 obstetricians/gynecologists per 100, 000 population. On average, there were 2 functioning operating rooms (ORs; OR in working condition that can be used for patient care) per hospital (standard deviation [SD] = 0.79; range, 1–3). Half of the hospitals surveyed had a postanesthesia care unit (PACU) and intensive care unit (ICU); however, only 1 hospital had mechanical ventilation capacity in the ICU. Ketamine and lidocaine were widely available. Intravenous (IV) morphine was always available in only 6 hospitals. None of the hospitals surveyed completely met the minimum World Health Organization (WHO)-WFSA standards for health care facilities where surgery and anesthesia are provided. CONCLUSIONS: Overall, we noted several critical gaps in anesthesia and surgical capacity in Liberia, in spite of the massive global response post-Ebola directed toward health system development. Further investment across all domains is necessary to attain minimum international standards and to facilitate the provision of safe surgery and anesthesia in Liberia. The study results will be considered in development of an NSOAP for Liberia.